INFRASTRUCTURAL DEVELOPMENT AND ITS EFFECT ON ECONOMIC GROWTH: THE NIGERIAN PERSPECTIVE - Olufemi, Edun Adetunji; Olatunbosun, Akinde Jubril; Olasode, Olaleye Samuel; Adeniran, Idowu Gbolahan (European Scientific Journal, ESJ, 2013)
This paper has attempted infrastructural development and its effect on economic growth: The Nigerian perspective. In Nigeria under investment in infrastructural development could be a bane to her vision of becoming a top 20 economy by the year 2020. Despite her economic growth over the years, this has not translated to economic development due to lack of infrastructure, high poverty rate, unemployment etc. The methodology adopted for this paper is a simple model of an economy with foreign investment and public infrastructure with a diversified equilibrium where the model is used to examine the impact of increased labor on production of private goods, public infrastructure, foreign investment, welfare and complete specialization. The paper went on further to advice the nation on measures to take to accelerate economic development, as economic growth alone is not enough.